2012
DOI: 10.1016/j.chembiol.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Evolved Stereoselective Hydrolases for Broad-Spectrum G-Type Nerve Agent Detoxification

Abstract: A preferred strategy for preventing nerve agents intoxication is catalytic scavenging by enzymes that hydrolyze them before they reach their targets. Using directed evolution, we simultaneously enhanced the activity of a previously described serum paraoxonase 1 (PON1) variant for hydrolysis of the toxic S(P) isomers of the most threatening G-type nerve agents. The evolved variants show ≤340-fold increased rates and catalytic efficiencies of 0.2-5 × 10(7) M(-1) min(-1). Our selection for prevention of acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 39 publications
0
80
0
Order By: Relevance
“…Their abundant expression allows αE7 CBEs to act as scavengers for OPs, sequestering the poison and slowly detoxifying it. Although the turnover rates of OPs by LcαE7 are currently much lower than other enzymes that have been engineered for OP hydrolysis (38), its high affinity for OPs makes LcαE7 a good starting point for the development of a high-specificity enzyme for OP poisoning. Indeed, in its native host, the G137D mutation is seen to increase the rate of OP turnover by two orders of magnitude, resulting in a large protective effect (4).…”
Section: Resultsmentioning
confidence: 99%
“…Their abundant expression allows αE7 CBEs to act as scavengers for OPs, sequestering the poison and slowly detoxifying it. Although the turnover rates of OPs by LcαE7 are currently much lower than other enzymes that have been engineered for OP hydrolysis (38), its high affinity for OPs makes LcαE7 a good starting point for the development of a high-specificity enzyme for OP poisoning. Indeed, in its native host, the G137D mutation is seen to increase the rate of OP turnover by two orders of magnitude, resulting in a large protective effect (4).…”
Section: Resultsmentioning
confidence: 99%
“…Our results identified that VII-D11 has the highest catalytic efficiency of the variants tested against paraoxon. Although further rounds of selection beyond VII-D11 gave rise to variants such as I-F11 and VII-D2 with increased activity toward the P (-)-isomer of each G agent (Goldsmith et al, 2012), the enhancement in paraoxon hydrolysis obtained through the evolution of VII-D11 from G3C9 was lost. In each round of selection, variants were screened against compounds other than paraoxon.…”
Section: Discussionmentioning
confidence: 99%
“…A decade of work using DNA shuffling, library screening, and mutagenesis of PON1 led to the characterization of a number of evolved PON1 variants based on the recombinant variant G3C9 (Gupta et al, 2011;Goldsmith et al, 2012). One such variant, 4E9, increased the survival rate of mice when injected 6 hours before a GF-analog injection (Gupta et al, 2011), which suggests that one or more of the evolved PON1 variants could also offer prophylactic protection against authentic chemical warfare nerve agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[99] When PON1 was subjected to directed evolution to enhance its promiscuous paraoxonase activity, the variants had higher metal ion occupancy in the alternative metal binding site. [99,108] This alternative binding site, 1.8 Å away from the native site, is postulated to be the initiator of divergence in activity between lactonase and paraoxonase enzymes. The mutation of a histidine residue in the directed evolution of PON1 is thought to change the calcium ion binding position, optimising the ligating residues for paraoxon hydrolysis.…”
Section: Active Site Changes and Activity Divergencementioning
confidence: 99%